GOVERNMENT ACTIVITIES AND PSYCHO-SOCIAL FACTORS AS DETERMINANTS OF SOLID WASTE MANAGEMENT BEHAVIOUR IN SOUTH WESTERN NIGERIA (2014)
This study examined the influence of government activities (delineation of dumping sites, provision of bins and transportation facilities, environmental policy formulation, advocacy, establishment of regulatory agencies) and psycho-social factors (attitudinal disposition, aesthetic values, neighbourhood appreciation, income, family/unit size, cultural affiliation, academic qualification, knowledge and awareness of environmental education) on solid wastes management behaviour in Southwestern Nigeria. The descriptive survey research design was adopted. The multi-stage sampling procedure was used in selecting 2465 households, 310 commercial units and 370 institutions in the six state capitals in Southwestern Nigeria. Three instruments were used: Psycho-social Factors Scale (r=0.84), Government Activities Scale (r=0.73) and SWMB Scale (r=0.78). These were complemented with 18 sessions of Key Informant Interview with heads of households, commercial units and institutions. Two research questions were answered and four hypotheses tested at 0.05 level of significance. Data were subjected to descriptive statistics, Pearson product moment correlation, multiple regression and content analyses. Government activities and psycho-social factors jointly correlated significantly with SWMB among households (F(3, 2452)=16.834), commercial units (F(3, 306)=3.654) and institutions (F(3, 366)=18.288). Their relative contributions were: institutions (12.0%), households (2.0%) and commercial units (2.0%). Relatively, the independent factors predicted SWMB as follows: Households- psychological factors (β=.53), social factors (β=.039) and government activities (β=-.43); Commercial units- psychological factors (β =2.72), government activities (β=1.25) and social factors (β=.02); Institutions- psychological factors (β=.384), social factors (β=.35) and government activities (β=.06). Solid wastes management behaviour correlated significantly with households’ attitudinal disposition (r=.18) and neighbourhood appreciation (r=-.10) but aesthetic value did not. For commercial units, SWMB correlated significantly with all psychological factors: attitudinal disposition (r=.157), aesthetic value (r=.148) and neighbourhood appreciation (r=-.117) while for the institutions, SWMB also correlated significantly with all psychological factors: neighbourhood appreciation (r=-.35), attitudinal disposition (r=.30) and aesthetic value (r=.12). Significant difference existed in attitude to SWM among commercial units ( =2.50), institutions ( =2.25) and households ( =1.25). Also significant difference existed in general knowledge about SWM among households ( =2.75), commercial units ( =2.25) and institutions ( =2.25). Although households had a better SWM awareness, they had poor attitude compared to commercial units and institutions. Interviews revealed that urban dwellers were kn owledgeable about SWM but had poor disposition to its management due to long-standing tradition. Delineation of dumping sites, provision of bins, attitudinal disposition and knowledge of environmental education positively determined solid waste management behaviour among households, industrial and institutional organisations. Therefore, urban dwellers’ disposition towards proper management of solid wastes needs to change, while all the strategies to improve SWMB must take into consideration these identified factors.